2016
DOI: 10.1093/dnares/dsw028
|View full text |Cite
|
Sign up to set email alerts
|

A systems-oriented analysis of the grapevine R2R3-MYB transcription factor family uncovers new insights into the regulation of stilbene accumulation

Abstract: R2R3-MYB transcription factors (TFs) belong to a large and functionally diverse protein superfamily in plants. In this study, we explore the evolution and function of this family in grapevine (Vitis vinifera L.), a high-value fruit crop. We identified and manually curated 134 genes using RNA-Seq data, and named them systematically according to the Super-Nomenclature Committee. We identified novel genes, splicing variants and grapevine/woody-specific duplicated subgroups, suggesting possible neo- and sub-functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
163
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 126 publications
(165 citation statements)
references
References 91 publications
(147 reference statements)
2
163
0
Order By: Relevance
“…This suggests that the C1 motif also is required for activity functional repressor. However, it is worth noting that the C1 motif also is found in the AtMYB5 homologs which have an activation role and belong to the MAV clade (Wong et al, 2016).…”
Section: New Phytologistmentioning
confidence: 99%
“…This suggests that the C1 motif also is required for activity functional repressor. However, it is worth noting that the C1 motif also is found in the AtMYB5 homologs which have an activation role and belong to the MAV clade (Wong et al, 2016).…”
Section: New Phytologistmentioning
confidence: 99%
“…influx, a MAPK cascade, and JA signaling but not SA were involved in the MYB14 transcriptional activation. A systems-oriented analysis performed by Wong et al (2016) revealed that the V. vinifera VvMYB14 and VvMYB15 genes share common co-expressed STS genes with the VvMYB13 gene, which is the uncharacterized closest homologue of VvMYB15. In a recent study, the MYB1 gene of V. amurensis (99% homology to VvMYB15 at the protein level) has been cloned and overexpressed in t-resveratrol-producing callus cell cultures of V. amurensis .…”
Section: Transcriptional Regulation Of Stilbene Biosynthesis In Plantsmentioning
confidence: 99%
“…Representation analysis of the MapMan BIN terms for their TOP100 co-expressed genes showed that several MYB genes were highly associated with terpenes (Wong et al, 2016). Thus, it is expected that some of these may directly regulate TPS or other genes of the isoprenoid pathway, as occurs with flavonoids or stilbenoids.…”
Section: Transcriptional Regulation Of Uv-induced Metabolic Responsesmentioning
confidence: 99%